2023
DOI: 10.1038/s41467-022-35359-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related matrix stiffening epigenetically regulates α-Klotho expression and compromises chondrocyte integrity

Abstract: Extracellular matrix stiffening is a quintessential feature of cartilage aging, a leading cause of knee osteoarthritis. Yet, the downstream molecular and cellular consequences of age-related biophysical alterations are poorly understood. Here, we show that epigenetic regulation of α-Klotho represents a novel mechanosensitive mechanism by which the aged extracellular matrix influences chondrocyte physiology. Using mass spectrometry proteomics followed by a series of genetic and pharmacological manipulations, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 90 publications
3
39
0
Order By: Relevance
“…We first performed an unbiased Kyoto Encyclopedia of Genes and Genomes (KEGG) Pathway Analysis using ROnToTools. ( 49 ) In the non-menopause group, the only pathway changing across time was Complement and coagulation cascades ( Figure 4B, S4A ), consistent with a previous report( 35 ). Conversely, in the menopause group, changes were progressive.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We first performed an unbiased Kyoto Encyclopedia of Genes and Genomes (KEGG) Pathway Analysis using ROnToTools. ( 49 ) In the non-menopause group, the only pathway changing across time was Complement and coagulation cascades ( Figure 4B, S4A ), consistent with a previous report( 35 ). Conversely, in the menopause group, changes were progressive.…”
Section: Resultssupporting
confidence: 88%
“…These findings suggest that menopausal aging induces progressive cartilage degeneration, while non-menopausal aging does not and are in line with previous work. ( 35 ) Additionally, the OARSI scores in the menopause, but not the non-menopause, group are in line with radiographic tracking of cartilage degeneration in women( 3639 ), suggesting the menopause group presents with a representative phenotype of KOA in women.…”
Section: Resultsmentioning
confidence: 55%
“…ECM remodeling is a widely-recognized cause of ECM stiffening 98 . In turn, ECM stiffening is a known driver of chondrocyte dysfunction and disrupted cartilage integrity via mechanotransductive pathways, both in the post-traumatic KOA in young mice 37 as well as naturally occurring KOA in aged mice 99 . Studies have shown that traumatic injury in young murine knee joints display altered transcripts associated with ECM remodeling and induced ECM stiffening via LOX-mediated increased collagen crosslinking 30,37 .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, matrix alterations have recently been proposed to be a hallmark of aging 40 . It is well established that increased ECM stiffness disrupts chondrocyte functionality via mechanotransductive signals 37,[41][42][43] . We therefore sought to dissect biophysical from biochemical effects of the ECM.…”
Section: Cartilage-specific Network Analysis Identified Aberrant Ecm ...mentioning
confidence: 99%
See 1 more Smart Citation